2016
DOI: 10.1088/0031-9155/61/5/2177
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive planning strategy for high dose rate prostate brachytherapy—a simulation study on needle positioning errors

Abstract: The development of magnetic resonance (MR) guided high dose rate (HDR) brachytherapy for prostate cancer has gained increasing interest for delivering a high tumor dose safely in a single fraction. To support needle placement in the limited workspace inside the closed-bore MRI, a single-needle MR-compatible robot is currently under development at the University Medical Center Utrecht (UMCU). This robotic device taps the needle in a divergent way from a single rotation point into the prostate. With this setup, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The potential for real-time adaptation involves constantly optimizing the dose distribution after each catheter is either inserted (pre-treatment adaptation) or retrospectively delivered, by accounting for the new source positions measured by an IVST or IVD system (realtime in-vivo adaptive HDRPBT). 31,32 Although Borot de Battisti et al 32 showed an increase in clinically acceptable plans after adaptation during the catheter insertion phase of treatment, real-time in-vivo adaptive HDRPBT introduced by Koprivec et al 31 showed there was only a benefit for prostate coverage recovery, but was unable to account for excess dose delivered to OARs during the delivery phase of treatment. Therefore, there also needs to be a solution for when to interrupt treatment if errors occur between the catheter insertion phase and delivery phases of treatment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential for real-time adaptation involves constantly optimizing the dose distribution after each catheter is either inserted (pre-treatment adaptation) or retrospectively delivered, by accounting for the new source positions measured by an IVST or IVD system (realtime in-vivo adaptive HDRPBT). 31,32 Although Borot de Battisti et al 32 showed an increase in clinically acceptable plans after adaptation during the catheter insertion phase of treatment, real-time in-vivo adaptive HDRPBT introduced by Koprivec et al 31 showed there was only a benefit for prostate coverage recovery, but was unable to account for excess dose delivered to OARs during the delivery phase of treatment. Therefore, there also needs to be a solution for when to interrupt treatment if errors occur between the catheter insertion phase and delivery phases of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study identified a potential method for amending/adapting the treatment in real‐time. The potential for real‐time adaptation involves constantly optimizing the dose distribution after each catheter is either inserted (pre‐treatment adaptation) or retrospectively delivered, by accounting for the new source positions measured by an IVST or IVD system (real‐time in‐vivo adaptive HDRPBT) 31,32 . Although Borot de Battisti et al 32 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those events can lead to uncertainties and errors in the delivered dose to the planning target volume (PTV) and organs at risk (OARs). 11 To reduce those uncertainties, two methods are possible: (1) restraining at maximum the needle positioning errors and (2) dynamically updating the dose plan with feedback on the actual catheter locations as shown by Borot de Battisti et al 12 For that, the real-time determination of the needle position (consisting of tracking the needle during insertion and reconstructing the needle after insertion) is warranted.…”
Section: Introductionmentioning
confidence: 99%